Application of the temperature-sensitive paint method for quantitative measurements in water. (15th June 2021) - Lemarechal, J; Klein, C; Puckert, D K; Rist, U
Abstract: In this paper the characteristics of a Europium-based temperature-sensitive paint (TSP) in polyurethane (PUR) clear coat submerged in water are investigated. It is shown that the temperature sensitivity is not affected by water. However, the optical transmission of the PUR is reduced, which reduces the measurable emission of the TSP. Furthermore, a TSP measurement in the laminar water channel at the Institute of Aerodynamics and Gas Dynamics, University of Stuttgart, was set up. In this experiment the skin friction field for two types of roughness elements, i.e. a truncated cylinder and an array of cuboids, in a Blasius-like boundary layer is investigated. Additionally, the temperature field was recorded with sub-millimeter resolution while an artificial heat flux was applied. A modification of the Colburn analogy is used to derive the skin friction from the temperature measurement. Skin friction results derived from velocity measurements are in good agreement with the TSP results. The experimental setup provides a resolution of the temperature and skin friction measurement of ( Δ T ) min <   0.007 K and ( Δ τ ) min ⩽   4.01 × 10 − 5 N m −2 ( ⩽ 1 % skin friction of the undisturbed flow), respectively. Additionally the uncertainty of the temperature and skin friction measurement is analyzed.